ANALISIS KINERJA PROSES PENDIDIKAN DALAM PERSPEKTIF 7’S MC-KINSEY - Liana Ariesha Khoerudin; Pepen Supendi (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2022)
The effectiveness of a school organization is influenced by how appropriate its actions are to the environment because the environment is always changing. Therefore, in organizations, especially managers, they are required to always monitor environmental changes and respond appropriately through various adjustments, both regarding structure, technology, processes, and the behavior of each member towards better development. This study aims to analyze what factors are the sources and strengths for the development of school organizations using the 7S McKinsey Framework method. This research is a qualitative research using the 7S McKinsey Framework method approach, data collection is done by means of interviews and observations. The results found that the Tahfidz Qur'an Islamic Junior High School was able to survive by making breakthroughs of the innovation through creative ideas that were visionary, then supported by the full role of managers, knowledge and management skills of foundation coaches and school principals. So that it can develop across the comfort zone.